Prognostic and predictive value of gastric acid suppressants in the EORTC 1325/KEYNOTE-054 randomized phase III trial of pembrolizumab vs placebo in resected stage III melanoma - Emanuel Bührer; Nina Glassee; Michal Kicinski; Oliver J. Kennedy; Christian U. Blank; Georgina V. Long; Victoria G. Atkinson; Stéphane Dalle; Andrew M. Haydon; Andrey Meshcheryakov; Adnan Khattak; Matteo S. Carlino; et al. (EJC Skin Cancer)
Background: The gut microbiome plays a pivotal role in regulating immunity. Gastric acid suppressants (GAS) are known to alter the gut microbiome and might therefore modify response to immunotherapy in cancer patients. We estimated associations of GAS with recurrence-free survival (RFS) and distant metastasis-free survival (DMFS) in the EORTC 1325/KEYNOTE-054 trial. Methods: Patients with resected stage III melanoma were randomized to receive 200 mg of pembrolizumab or placebo. Pembrolizumab prolonged RFS and DMFS (reported elsewhere). We used Cox models to estimate hazard ratios (HR) and 95 % confidence intervals (CI) for the association between GAS at baseline, and RFS and DMFS, overall and by treatment arm. Results: Out of 1019 randomized patients, 109 (10.7 %) used GAS at baseline. We did not find a prognostic importance for RFS (HR 1.06, 95 % CI 0.79–1.42) or DMFS (HR 1.05, 95 % CI 0.77–1.43), neither a predictive importance (HR for RFS in the pembrolizumab arm: 1.02 (95 % CI 0.66–1.56) and 1.09 (95 % CI 0.74–1.62) in the placebo arm (p = 0.81); corresponding HRs for DMFS: 1.17 (95 % CI 0.75–1.82) and 0.95 (95 % CI 0.62–1.48) (p = 0.52)). Conclusion: GAS showed no impact on RFS or DMFS in patients with stage III melanoma receiving adjuvant pembrolizumab or placebo.